Comparative Analysis of Virtual Impedance Control Techniques for Improved Stability in DC Microgrids - Beatriz Cristina Moura; Danillo Borges Rodrigues; Erico Chagas Guimaraes; Gustavo Brito de Lima; Joao Pedro Carvalho Silveira; Luiz Carlos Gomes Freitas; Pedro Jose Dos Santos Neto (IEEE Access)
DC microgrids (DCMGs) have been extensively studied using various control techniques, with droop control and its variants being the most widely adopted. Virtual impedance control (VIC), a technique commonly used in AC microgrids, can be adapted for DCMGs. VIC employs virtual resistance as the droop constant and incorporates a dynamic element, such as a virtual inductor, to enhance microgrid stability. This study compares four approaches to implementing VIC to determine the most effective method for reducing voltage oscillations during transient conditions, which enhances overall DCMG stability. In this paper, the analyzed DCMG consists of two units of energy storage system (ESS), electronic loads, and a renewable energy source (RES), each connected via a dedicated power electronic converter. Parametric analyses are conducted to define the VIC parameter range, and a stability analysis is performed to evaluate the different methods of implementation. The techniques under analysis are tested using a controller hardware-in-the-loop (C-HIL). The results establish the operating range for each VIC strategy, the stability limitations, and identifying the control approach that achieves optimal damping performance and stability in the studied microgrid.